2016
DOI: 10.1080/02786826.2016.1173185
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of airflow and particle behavior around a subway train running in the underground tunnel

Abstract: Airflow around an eight-passenger-car subway train running in the underground tunnel at a cruise speed of 70 km/h was numerically simulated, and the trajectories of the particles that were assumed to be re-suspended from the ground or generated at the contact points between the wheels and rails were predicted. In addition, field experiments were conducted to measure airflow velocity and PM 10 mass concentration under a T-car (trailer car without a driving cab) during the running of a subway train in straight s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Cars 1 and 8 were TCCars, Cars 2 and 7 were M1-Cars, Cars 3 and 6 were M2-Cars, and Cars 4 and 5 were T-Cars. A three-dimensional view of this train can be found elsewhere (Lee et al, 2016). As illustrated in Fig.…”
Section: Numericalmentioning
confidence: 99%
See 2 more Smart Citations
“…Cars 1 and 8 were TCCars, Cars 2 and 7 were M1-Cars, Cars 3 and 6 were M2-Cars, and Cars 4 and 5 were T-Cars. A three-dimensional view of this train can be found elsewhere (Lee et al, 2016). As illustrated in Fig.…”
Section: Numericalmentioning
confidence: 99%
“…The convergence criteria were set at 10 -3 for the continuity and momentum equations and 10 -6 for the energy equation. A more detailed description of the numerical scheme employed in this study can be found in our previous publication (Lee et al, 2016).…”
Section: Numericalmentioning
confidence: 99%
See 1 more Smart Citation